Sustainability in Luxury Fashion Business (Springer Series in Fashion Business,, 2018)
This book explores new approaches and strategies that luxury fashion brands could adopt in their operations toward sustainability goals. It addresses the unique challenges faced by luxury fashion brands, given that concepts of luxury and sustainability may be conflicting. In doing so, it elaborates on how fashion brands need to manage their suppliers to comply with and improve social and environmental conditions, the pressure to fulfill the triple-bottom lines, consumer demands for transparency, and social media and its advantages in achieving sustainability goals. Exploring the notion that luxury fashion brands are in a better position to pursue superior sustainability performance, it presents research that highlights how the consequences of non-compliance could have more devastating effects on luxury brands than on mass-market brands. The book is a valuable resource for academics and practitioners in the field of business, sustainability, and fashion.